FAULT ANALYSIS ON NIGERIA 330kV TRANSMISSION SYSTEM USING ETAP (Nigerian Journal of Technology, 2018)
The 330kV transmission network is the back bone of the Nigeria power system as it connects all power plants and load centers in all parts of the country; hence its economic importance cannot be over emphasized. Fault occurrence in this network slows down economic and other sectorsâ€™ activities; hence proper plan should be put in place to protect the system from the adverse effect of these faults when they occur. This paper has presented the nature of the system when these faults occur in three Buses (4, 16 and 23 corresponding to Niger, Oshogbo and Alaoji respectively) by simulation in ETAP. The results also show that double line to ground, LLG (between line â€œaâ€ and â€œbâ€) fault at bus 23 produces a 0.0kV in the 2 affected lines but a high voltage of 112% of rated voltage at line â€˜câ€™ in the faulty bus 23. This same LLG fault at bus 16 produces similar result but a higher line â€˜câ€™ voltage of 131% of rated line voltage in the faulty bus 16. LL faults always result reduction in voltage of the two lines under fault. In bus 23, the line voltages of the affected lines were 49.32% of the rated line voltage. With this analysis, the behavior of the network when different faults occur at different locations has been known by the protection engineers, protecting the network can be a lot cheaper and effective making the system more reliable, effective and profitable. Keywords: Fault; Analysis; Transmission; System; ETAP. http://dx.doi.org/10.4314/njt.v38i1.25